Self-Assembled Monolayers Star-Shaped Crystallographic Cracking of Localized Nanoporous Defects (Adv. Mater. 33/2015) - Renner, Frank Uwe (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.